Current trend on the economic and public health significance of Salmonellosis in Iraq - Abdulhaleem, Noor; Garba, Bashiru; Younis, Hind; Mahmuda, Aliyu; Awang Hamat, Rukman; Abd. Majid, Roslaini; Than, Leslie Thian Lung; Unyah, Ngah Zasmy; Sattar, Abdul; Saidu, Mohammed Bashir (Nexus Academic Publishers, 2019)
Salmonellosis is reported as one of the main cause of diarrhoeal diseases globally. The disease is also associated with enteric fever, including typhoid which is a potentially fatal systemic illness bedeviling many developing countries. The disease is estimated to affect nearly 17 million people with over 150,000 deaths occurring annually. Salmonellosis is also beginning to emerge as a foodborne infection characterized by significant economic and public health hazard with global ramifications. High prevalence of the disease is directly related to poor sanitation and hygiene, consumption and use of unsafe water, overcrowding and social unrest. A significant number of Iraqis are affected annually with a death rate of 10-20 %, mainly resulting from limited access to fresh water and improper sewage disposal into the river bodies. This review provides an overview of Salmonella infection in human and animals, with emphasis on the economic and public health burden of the disease in Iraq.